SEJARAH PENEMPATAN DAN ADAPTASI LINGKUNGAN BARU TRANSMIGRAN JAWA BARAT DI KECAMATAN RASAU JAYA - Diah Trismi Harjanti (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2021)
The unequal distribution of the population in Indonesia is caused by the concentration of the population of Java, which led the government to create a population movement program called transmigration. The types of transmigration carried out by the Indonesian government are general transmigration and self-employment transmigration. West Borneo, which is the destination for transmigration, is Rasau Jaya District, Kubu Raya Regency. Of the six villages in the Rasau Jaya sub-district, there are only four villages that are the placement areas for transmigrants, namely Rasau Jaya Satu Village, Rasau Jaya Dua Village, Rasau Jaya Tiga Village and Bintang Mas Village. Rasau Jaya Tiga Village in 1975-1977 became the most transmigration destination area because it had the largest land area among other villages. The method used is descriptive with a qualitative approach and the object under study is the transmigrant who came from West Java.